Measurement of non-use value of Sand Lake wetland under CVM Method - Yan, Xiaohan; Lee, Chin; Muhamad Senan, Mohamad Khair Afham (Human Resource Management Academic Research Society, 2023)
The Sand Lake wetland, located in inland northwestern region of China within Ningxia Province, is a national notable tourist attraction with natural landscape. It is also known as a rare cultural tourist resort in the world. However, rather than just emphasizing on its economic use, non-use value could represent people's consideration of the emotional, cultural, and ecosystem services of the Sand Lake wetland, with significance in water source protection and climate regulation. Therefore, this article utilized the Conditional Value Method (CVM) to evaluate the non-use value of the Sand Lake wetland. A questionnaire survey of year-round residents in the Ningxia province was conducted and found that the non-use value of Sand Lake was 638.145 million RMB. Then, Ordinal Logistic Regression was adopted to analyze the relationship between the social status of respondents and their willingness to pay. It was found that the higher the income and the frequencies of the respondents touring the wetland, the higher their willingness to pay for the non-market value of the Ningxia Sand Lake wetland.